Reliability of synovial fluid alpha-defensin and leukocyte esterase in diagnosing periprosthetic joint infection (PJI): a systematic review and meta-analysis - Chen, Yisheng (J Orthop Surg Res, 2019)
BACKGROUND: Synovial fluid proteins had been applied as diagnostic biomarkers for periprosthetic joint infection (PJI) in recent research papers. Thus, this meta-analysis aimed to estimate the diagnostic efficiency of synovial fluid α-defensin and leukocyte esterase (LE) for PJI. METHODS: We conducted our systematic review by searching the keywords in online databases such as PubMed, Embase, Cochrane, Elsevier, Springer, and Web of Science from the time of database inception to October 2018. Inclusion criteria were as follows: patients who have undergone knee, hip, or shoulder joint replacements; α-defensin or leukocyte esterase (LE strip) of synovial fluid was detected as the biomarker for PJI diagnosis; and Musculoskeletal Infection Society (MSIS) or utilizing a combination of clinical data was considered as the gold standard. Diagnostic parameters including sensitivity, specificity, diagnostic odds ratio (DOR), and area under the summary of receiver operating characteristics curve (AUSROC) were calculated for the included studies to evaluate the synovial fluid α-defensin and LE for PJI diagnosis. RESULTS: After full-text review, 28 studies were qualified for this systematic review, 16 studies used α-defensin and the other 12 were conducted using LE strip. The pooled sensitivity, specificity, and DOR of LE strip were 87% (95% CI 84–90%), 96% (95% CI 95–97%), and 170.09 (95% CI 97.63–296.32), respectively, while the pooled sensitivity, specificity, and DOR of α-defensin were 87% (95% CI 83–90%), 97% (95% CI 96–98%), and 158.18 (95% CI 74.26–336.91), respectively. The AUSROC for LE strip and α-defensin were 0.9818 and 0.9685, respectively. CONCLUSION: Both LE strip and α-defensin of synovial fluid provide rapid and convenient diagnosis for PJI. Sensitivity of α-defensin and LE strip are the same, while both these two methods have high specificity in clinical practice.